2021
DOI: 10.3390/land10050469
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Water Conflicts: A Comprehensive Review of MCDM Approaches to Manage Freshwater Ecosystem Services

Abstract: This paper presents a comprehensive review of the application of Multiple-Criteria Decision-Making (MCDM) approaches exclusively to water-related freshwater ecosystem services. MCDM analysis has been useful in solving conflicts and it works well in this framework, given the serious conflicts historically associated with water use and the protection of freshwater ecosystems around the world. In this study, we present a review of 150 papers that proposed the use of MCDM-based methods for the social, economic, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…To this end, multi-criteria (decision) analysis (MCA) is considered a suitable framework (Langemeyer et al, 2016;Saarikoski et al, 2016), and is increasingly applied in water-related management contexts (e.g. Castro-Pardo et al, 2021;Martínez-López et al, 2019;Marttunen et al, 2022). Drawing on such approaches, this article presents a conceptual framework for ES valuation in the context of mountain lakes using the PROMETH-EE method.…”
Section: Developing Es Indicators and Integrative Valuationmentioning
confidence: 99%
“…To this end, multi-criteria (decision) analysis (MCA) is considered a suitable framework (Langemeyer et al, 2016;Saarikoski et al, 2016), and is increasingly applied in water-related management contexts (e.g. Castro-Pardo et al, 2021;Martínez-López et al, 2019;Marttunen et al, 2022). Drawing on such approaches, this article presents a conceptual framework for ES valuation in the context of mountain lakes using the PROMETH-EE method.…”
Section: Developing Es Indicators and Integrative Valuationmentioning
confidence: 99%
“…de Castro-Pardo et al [30] focused on reviewing nearly 150 papers related to water ecosystem planning and management between 2000 to 2020 which had used various MCDM algorithms for the analysis. Their results showed that most of papers in this field only focused on investigating the factors impacting on water consumption and there were a few papers discussing on managerial aspects of water shortage issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the prospect of billions of people facing serious water scarcity problems and associated food shortages, the management of water as a resource requires urgent strategic action. Currently two billion people live in countries with large water deficits and by 2030, 700 million people are expected to be displaced by intense water scarcity (de Castro-Pardo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%